Population mobility and COVID-19 incidence in Indonesia: a study from North Sulawesi Province - Dampi, Denada Jihan; Kalesaran, Angela Fitriani Clementine; Kandou, Grace Debbie (BKM Public Health and Community Medicine, 2024)
Purpose: The purpose of the study is to determine the relationship between the level of population mobility and the incidence of COVID-19 in 2021 in the North Sulawesi province. Methods: This quantitative research uses an ecological study. This study used secondary data from Google Mobility Reports and COVID-19 incidence data from the North Sulawesi Province Health Department. Univariate analysis describes population mobility variables in various sectors and the incidence of COVID-19, which is presented as a time series graph. In contrast, bivariate analysis is used to test the relationship between the level of mobility in various sectors and the incidence of COVID-19 through non-parametric analysis with the Spearman Rank correlation test. Results: There is a correlation between the incidence of COVID-19 and the level of mobility, with a p-value <0.05, with different levels of correlation amongst each mobility area. The correlation coefficients (r) between the incidence of COVID-19 and various regions of mobility are as follows: retail and recreation (-0.511), wholesale and pharmaceuticals (-0.398), park (-0.454), transportation (-0.570), workplace (-0.332), and housing (0.641). Conclusion: The increase in population mobility has significantly contributed to the high incidence of COVID-19 in North Sulawesi in 2021. To reduce the incidence of COVID-19, strict policies for monitoring and controlling mobility, especially in areas with high mobility, are necessary.